2022
DOI: 10.3390/cancers14153754
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Gene Expression-Based Signature in Clear-Cell Renal Cell Carcinoma

Abstract: The inaccuracy of the current prognostic algorithms and the potential changes in the therapeutic management of localized ccRCC demands the development of an improved prognostic model for these patients. To this end, we analyzed whole-transcriptome profiling of 26 tissue samples from progressive and non-progressive ccRCCs using Illumina Hi-seq 4000. Differentially expressed genes (DEG) were intersected with the RNA-sequencing data from the TCGA. The overlapping genes were used for further analysis. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Consistently, the current study also showed that GNLY is specifically expressed in bladder cancer T cells. CERCAM is an adhesion molecule whose expression is at high levels in brain microvasculature, which leukocytes can use to stretch across the blood–brain barrier, regulate leukocyte migration capacity and adhesion, and has been found to be a negative prognostic marker in several tumors 41 43 . Its overexpression promotes cell viability, proliferation, and invasion and is associated with the PI3K/AKT pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the current study also showed that GNLY is specifically expressed in bladder cancer T cells. CERCAM is an adhesion molecule whose expression is at high levels in brain microvasculature, which leukocytes can use to stretch across the blood–brain barrier, regulate leukocyte migration capacity and adhesion, and has been found to be a negative prognostic marker in several tumors 41 43 . Its overexpression promotes cell viability, proliferation, and invasion and is associated with the PI3K/AKT pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…CERCAM, as a gene associated with cell adhesion as well as extracellular matrix remodeling, its role in tumors is mainly to promote tumor epithelial cell migration and promote cancer progression(46). Although it has been found that the expression level of CERCAM in Colon Cancer and kidney cancer affects the prognostic level of tumors (47,48). However, in head and neck squamous carcinoma, the prognostic signi cance and biological functions of CERCAM have never been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, PD-L1 expression status was analyzed in tumor-infiltrating immune cells but not in tumor cells. Factors that were not considered in this study, such as PD-L1 expression status in tumor cells and gene expression [ 31 , 32 ] or mutation analysis, should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%